2016
DOI: 10.1111/hex.12498
|View full text |Cite
|
Sign up to set email alerts
|

Health information sources for different types of information used by Chinese patients with cancer and their family caregivers

Abstract: ContextLittle is known about the information sources of Chinese patients with cancer and their family caregivers, yet this knowledge is critical for providing patient‐centred care.ObjectiveTo assess and compare the information sources used by Chinese patients with cancer and their family caregivers.DesignThe validated Health Information Wants Questionnaire (HIWQ) was translated and administered in March 2014.SettingThe oncology department of a general hospital in south‐west China.ParticipantsA convenience samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 36 publications
0
18
0
Order By: Relevance
“…While information needs decrease over time, some carers still experience unmet information needs throughout treatment and at the end of treatment . Carers have used a variety of sources to address their unmet needs, most commonly relying on healthcare professionals, family, friends, and the internet . However, current methods of delivering information are often inadequate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While information needs decrease over time, some carers still experience unmet information needs throughout treatment and at the end of treatment . Carers have used a variety of sources to address their unmet needs, most commonly relying on healthcare professionals, family, friends, and the internet . However, current methods of delivering information are often inadequate.…”
Section: Introductionmentioning
confidence: 99%
“…9 Carers have used a variety of sources to address their unmet needs, most commonly relying on healthcare professionals, family, friends, and the internet. 10 However, current methods of delivering information are often inadequate. Oberoi et al 8 for example found that out of 196 carers, only 33% were certain that they received information on managing patients' symptoms and only 18% were asked by nursing staff if they required more support.…”
mentioning
confidence: 99%
“…This study contributes to the literature by investigating the access/use patterns among 25 health information sources including health professionals, lay individuals, mass media, and different types of online sources (eg, social media, medical websites, and blogs or celebrity webpages). We explored a wide range of health information sources because consumers report consulting multiple kinds of sources for information when making health decisions . For example, individuals tend to use health professionals for information related to diagnosis or standard treatment, but they use friends for information related to coping strategies .…”
mentioning
confidence: 99%
“…We explored a wide range of health information sources because consumers report consulting multiple kinds of sources for information when making health decisions . For example, individuals tend to use health professionals for information related to diagnosis or standard treatment, but they use friends for information related to coping strategies . Also, many previous studies categorized online health information sources as a single source, rather than differentiating between types of online sources; however, the use patterns vary among medical websites, social media, and celebrity webpages .…”
mentioning
confidence: 99%
See 1 more Smart Citation